Asymptomatic Bacteriuria in Pregnant and Diabetic Women - Manhal, Falah Salim; Gauad, Shaymaa Ali (AL-Kindy College Medical Journal, 2011)
Background: Asymptomatic bacteriuria (ASB) is defined as isolation of a specified quantitative count of bacteria in an appropriately collected urine specimen from an individual without symptoms or signs of urinary tract infection. Aim of study: To evaluate the frequency of bacteriuria according to age, pregnancy, and type II diabetes mellitus in a sample of Iraqi women. Patients and Methods: A total of 125 female individuals were involved. The study participants were classified into the following groups: nonpregnant women with type II diabetes mellitus, pregnant women with type II diabetes mellitus, pregnant women without type II diabetes mellitus, and apparently healthy non-pregnant women. Urine and blood specimens were tested to record positive urine culture, pyuria, and blood glucose according to standard microbiological and biochemical methods. Results: Frequency of positive urine culture and pyuria in the total pregnant women was 7 (14%) and 15 (30%), respectively, whereas frequency of positive urine culture and pyuria in the total diabetic women was 8 (16%) and 23 (46%), respectively. The bacterial isolation rate in the studied groups was 13 (10%). Ecoli recorded the highest isolation rate, 6(5%). There was no significant culture positive of urine specimens in the groups of diabetic non-pregnant, diabetic pregnant, and women with normal pregnancy (Pvalue< 0.05). Pregnant women with culture positive urine and pyuria were more likely to have perinatal mortality. Sterile pyuria was detected in pregnant women aged 18-45, those in third trimester, and in multiparous pregnant women. There was significant positive urine culture and a highly significant pyuria in diabetic women with BMI > 25. Conclusions: Asymptomatic bacteriuria is an independent risk factor for perinatal mortality. Sterile pyuria is a significant observation in pregnant and diabetic women; therefore it should bring more attention. Recommendations Treatment of asymptomatic bacteriuria is appropriate for pregnant women but it is not recommended for diabetics. The study advised to perform urine culture as a part of the antenatal checkup for pregnant women.